Physical Therapy in the Management of Pelvic Floor Muscles Hypertonia in a Woman with Hereditary Spastic Paraplegia - Aline Moreira Ribeiro; Cristine Homsi Jorge Ferreira; Elaine Cristine Lemes Mateus-Vasconcelos; Rafael Mendes Moroni; Luciane Maria Oliveira Brito; Luiz Gustavo Oliveira Brito (Case Reports in Obstetrics and Gynecology)
Background. Pelvic floor (PF) hypertonic disorders are a group of conditions that present with muscular hypertonia or spasticity, resulting in a diminished capacity to isolate, contract, and relax the PF. Their presentation includes voiding and sexual dysfunctions, pelvic pain, and constipation. Various factors are associated, such as complicated vaginal birth, muscular injury, scar tissue formation, and neuropathies. Study Design. The case of a single patient will be presented, together with the management strategies employed. Case Description. A woman with hereditary spastic paraparesis and a history of muscle spasticity and urinary and fecal complaints since childhood. She presented to this institution seeking treatment for pelvic pain, pain during intercourse, constipation, and micturition problems. A physical therapy protocol was developed, with the trial of several treatment modalities. Outcome. After some failed attempts, perineal and pelvic floor stretching proved to be very efficacious therapies for this patient’s complaint, leading to improved pain during intercourse, constipation, pelvic pain, and urinary stream. Discussion. PF spasticity can lead to severe disability and interfere with daily basic functions, such as micturition and evacuation. Physical therapy plays an essential role in the management of these patients and can lead to significant improvement in quality of life.